2020
DOI: 10.1088/1361-6595/abb21a
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a thermionic plasma source apparatus for high-density gaseous plasma antenna applications

Abstract: A thermionic plasma source apparatus has been developed and characterised for high-density gaseous plasma antenna (GPA) applications. The system produces a cylindrical plasma column which is 100 mm long with a diameter of 8 mm and operates with a total plasma power consumption of 70 to 200 W, depending mainly on the DC discharge current. The plasma column electron density and temperature is measured via microwave interferometry and optical emission spectroscopy. The plasma properties are investigated for Ar, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…Moreover, the selection of COTS can be tailored to different customers' needs by means of a dedicated risk analysis. The electronics rely on a flexible architecture and they have been designed for operating REG-ULUS with an input power from 30 up to 60 W, although the nominal value is 50 W. Moreover, a simplified laboratory version of the electronics subsystem has been used in a completely different application field, namely plasma antennas [45][46][47][48]. The schematic of the electronics of REGULUS is depicted in Fig.…”
Section: Electronicsmentioning
confidence: 99%
“…Moreover, the selection of COTS can be tailored to different customers' needs by means of a dedicated risk analysis. The electronics rely on a flexible architecture and they have been designed for operating REG-ULUS with an input power from 30 up to 60 W, although the nominal value is 50 W. Moreover, a simplified laboratory version of the electronics subsystem has been used in a completely different application field, namely plasma antennas [45][46][47][48]. The schematic of the electronics of REGULUS is depicted in Fig.…”
Section: Electronicsmentioning
confidence: 99%
“…Taking into account the plasma source’s rigid structure and by electromagnetically shielding most of its metallic parts through an additional metallic cover, the current plasma source is considered to approximate a quarter-wave monopole antenna that is placed perpendicular against a conducting ground plane. In fact, this plasma antenna exhibits electromagnetic characteristics and operation rather close to that of a conventional metallic quarter-wave monopole antenna of similar dimensions (Daykin-Iliopoulos et al , 2020).…”
Section: Antenna Configurationmentioning
confidence: 80%
“…A single element of the antenna under consideration is based on the hollow cathode thermionic plasma source described in Daykin-Iliopoulos et al (2020) and shown in Figure 1. Its function relies on the high-density gaseous plasma column that has the substantial advantage of being able to rapidly and effectively turn ON, meaning high-density plasma with electromagnetic parameters close to that of metals, and OFF, meaning complete absence of conductive materials along the main column.…”
Section: Antenna Configurationmentioning
confidence: 99%
See 2 more Smart Citations